(untitled) (American Journal of Islam and Society, 2009)
This conference (www.iranoworld.ir), the first one to be organized by the faculty of the Department of Political Science at Imam Khomeini International University (IKIU) and will be held continuously in the following years, sought to develop knowledge and making the ground suitable for discussing and analyzing the work of researchers both inside and outside Iran. Despite the antiquity of Iran’s history, rich oil and gas resources, and monitoring of the strategic Persian Gulf, the country has enjoyed stability in its blend of religion and politics of social affairs in the face of profound change. Contemporary international relations, known for its dominating principles of equal sovereignty and self-determination, is also undergoing change, the most obvious ones being the Soviet collapse, the “new world order,” and globalization, all of which have affected Iran ...